2018
DOI: 10.1177/1747954118788449
|View full text |Cite
|
Sign up to set email alerts
|

Game-play characteristics differ between the European Super League and the National Rugby League: Implications for coaching and talent recruitment

Abstract: Objectives To compare the game-play characteristics between the European Super League and the National Rugby League competitions. Methods Eleven team performance indicators were extracted from each match played by every European Super League and National Rugby League team over their respective 2016 season. Data were averaged, classified according to competition (two levels: European Super League and National Rugby League) and modelled using univariate and multivariate techniques. Specifically, effect size stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 12 publications
2
19
0
Order By: Relevance
“…From these 39 studies, participants were drawn from teams in the NRL, SL, Australian State Leagues (predominantly the Queensland Cup [QCup]), International, Australian Under 20's National Youth Competition (NYC), and amateur competitions (see Table 2). The remaining four studies reported on participants with collisions analysed via video footage at the competition level [1,28,41,68].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…From these 39 studies, participants were drawn from teams in the NRL, SL, Australian State Leagues (predominantly the Queensland Cup [QCup]), International, Australian Under 20's National Youth Competition (NYC), and amateur competitions (see Table 2). The remaining four studies reported on participants with collisions analysed via video footage at the competition level [1,28,41,68].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Of the studies that compared cohorts between competition standards, one study compared cohorts from the NRL to Qcup [71], one study compared NRL cohorts to NSWCup [32], two studies compared NRL to SL [1,65], two studies compared NRL to NYC [23,68], and one study compared international to NRL [41]. Studies typically compared the collision dose either at the overall team level or within positional groupings.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies have employed multivariate modelling such as nMDS to investigate match play differences across seasons and/or competitions in various sports such as Netball [18], Rugby League [19] and Australian Football [16]. This non-linear approach has clearly shown the idiosyncrasy of teams' performances and provided a unique examination and visualization of sporting evolution [16,18,19]. Further, it has identified team adaptations employed by successful teams that could be utilised by others to enhance future success [18,19].…”
Section: Introductionmentioning
confidence: 99%